(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The issue of gratuitous youth violence is a pressing public health concern and a symptom of weakened social cohesion. Social medicine frames it as a collective phenomenon shaped by inequalities, education, employment, social capital, and marginalisation. Research shows a correlation between declining community cohesion and institutional trust, on one hand, and rising antisocial and aggressive behaviours, on the other, especially among youth. This study highlights the role of social determinants while underscoring critical-reflective thinking as a protective factor. Drawing on Aristotelian perspectives, critical thinking is presented as an ethical safeguard, fostering responsibility, relational health, and primary prevention.